Green synthetic approaches for biologically relevant heterocycles - Brahmachari, Goutam (Amsterdam ; Waltham, Mass. : Elsevier Science, 2015)
Green Synthetic Approaches for Biologically Relevant Heterocycles reviews this significant group of organic compounds within the context of sustainable methods and processes. Each clearly structured chapter features in-depth coverage of various green protocols for the synthesis of a wide variety of bioactive heterocycles classified on the basis of ring-size and/or presence of heteratoms(s). Techniques covered include microwave heating, ultrasound, ionic liquids, solid phase, solvent-free, heterogeneous catalysis, and aqueous media, along with multi-component reaction strategies. This book also integrates advances in green chemistry research into industrial applications and process developments. Green Synthetic Approaches for Biologically Relevant Heterocycles is an essential resource on green chemistry technologies for academic researchers, R & D professionals, and students working in medicinal, organic, natural product, and agricultural chemistry.
CHAPTER 8 -- Green Synthetic Approaches forBiologically Relevant 2-amino-4H-pyransand 2-amino-4H-pyran-Annulated Heterocyclesin Aqueous Media1. INTRODUCTION; 2. SYNTHETIC APPROACHES FOR 2-AMINO-4H-PYRANS AND 2-AMINO-4H-PYRAN-ANNULATED HETEROCYCLES IN WATER AND ETHANOL-WATER MEDIA; 3. CONCLUDING REMARKS; Acknowledgments; References; Chapter 9 -- Sustainable Synthesis of Benzimidazoles, Quinoxalines, and Congeners; 1. INTRODUCTION; 2. METHODS OF SYNTHESIS OF BENZIMIDAZOLES/QUINOXALINES USING GREENER STRATEGIES; 3. CONCLUDING REMARKS; References.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed November 20, 2014).
Keywords: Heterocyclic compounds; Green chemistry; SCIENCE -- Chemistry -- Organic; Green chemistry; Heterocyclic compounds; Electronic books